2007
DOI: 10.4269/ajtmh.2007.76.450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deforestation and Agricultural Development on Anopheline Ecology and Malaria Epidemiology

Abstract: To clarify mechanisms linking deforestation, anopheline ecology, and malaria epidemiology, this study draws together 60 examples of changes in anopheline ecology and malaria incidence as a consequence of deforestation and agricultural development. The deforestation projects were classified based on subsequent land use and were reviewed in terms of their impact on anopheline density and malaria incidence. To further examine different anopheline responses to land transformation, two major ecological characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
213
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(229 citation statements)
references
References 58 publications
(49 reference statements)
10
213
0
6
Order By: Relevance
“…They also increase exposure to other vector-borne diseases associated with significant morbidity and mortality including Rift Valley fever, filariasis, leishmaniasis, dracunculosis, onchocerciasis, and Japanese encephalitis (13)(14)(15)(16). Deforestation increases exposure to malaria in Africa (17)(18)(19)(20)(21) and South America (20)(21)(22)(23)(24)(25)(26) but has less predictable impacts in Asia (27)(28)(29)(30)(31) where there are many more Anopheles vectors with less generalizable responses to reduced forest cover. In parts of Africa, forest cutting also alters the composition and density of aquatic snail species in a manner that favors transmission of schistosomiasis (32).…”
Section: Highlights Of the Recent Literaturementioning
confidence: 99%
“…They also increase exposure to other vector-borne diseases associated with significant morbidity and mortality including Rift Valley fever, filariasis, leishmaniasis, dracunculosis, onchocerciasis, and Japanese encephalitis (13)(14)(15)(16). Deforestation increases exposure to malaria in Africa (17)(18)(19)(20)(21) and South America (20)(21)(22)(23)(24)(25)(26) but has less predictable impacts in Asia (27)(28)(29)(30)(31) where there are many more Anopheles vectors with less generalizable responses to reduced forest cover. In parts of Africa, forest cutting also alters the composition and density of aquatic snail species in a manner that favors transmission of schistosomiasis (32).…”
Section: Highlights Of the Recent Literaturementioning
confidence: 99%
“…The thin evidence base focuses on specific drivers of specific diseases (6), typically climate (20)(21)(22)(23)(24)(25), biodemography and migration (13,(26)(27)(28)(29)(30), or land-use change (20,(31)(32)(33). Expanding this literature into multifactorial analyses could provide a more comprehensive picture of the human ecology of these diseases, including the role of specific behaviors and policies (8,34).…”
mentioning
confidence: 99%
“…In 1981, the construction of the Tucuruí hydroelectric dam in southeast Pará province, Brazil, caused enormous environmental changes, deforestation, and human migration to the region, and a study 30 confirmed the elevation of malaria to the epidemic level since then. In a review of the literature 27 , sixty examples of changes in anopheline ecology throughout the tropical world were identified as a consequence of deforestation and agricultural development.…”
Section: Discussionmentioning
confidence: 99%
“…The year-round high rainfall and temperatures in tropical forests are ecological characteristics that favor the development of many kinds of mosquitoes that transmit pathogens that cause disease in humans 26 . Thus, the process of clearing forests and the subsequent human activities, such as agricultural and hydropower developments, have a high influence on the prevalence and incidence of diseases such as human malaria 27 . In a study that examined the ecological alteration in the Peruvian Amazon 28 , it was shown that various landscapes and ecological features associated with deforestation were positively associated with Anopheles darlingi larval breeding sites.…”
Section: Discussionmentioning
confidence: 99%